Analisis dan Perancangan Sistem Informasi Manajemen pada Akademis AMIK ASM LAKSI 31 - Inayatulloh Inayatulloh (Bina Nusantara University, 2011)
The purpose of this article is to develop a computer-based Academic management information system for AMIK LAKSI 31 ASM by using Internet technology which functions to integrate internal processes with the academic learning process. The method of this research includes analysis of campus internal administration process of teaching and learning and development of a computer-based application that supports the process. In analyzing the campus administrative processes, several activities are carried out in order to get both information required and design of application built in accordance with needs. The result obtained is an academic information system model to be used in ASM AMIK LAKSI 31 based on web that can help the institution to improve efficiency and effectiveness of administrative processes and learning process.